2008
DOI: 10.1111/j.1747-4477.2007.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular molar with five root canals

Abstract: The purpose of this study was to demonstrate the importance of knowledge of the internal anatomy of root canals for the success of endodontic treatment. Lack of knowledge of anatomic variations and their characteristics in different teeth has been pointed out as one of the main causes of endodontic therapy failure. In this report, the authors describe the endodontic treatment of a mandibular first molar with five root canals, evaluate the rate of occurrence of this number of canals, and discuss the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Unusual root and root canal morphologies associated with molars have been recorded in several studies in the literature (2)(3)(4). Pécora et al (4) evaluated the anatomy of 370 maxillary molars and found that the maxillary first, second, and third molars showed three canals in 75%, 58%, and 68% of the teeth, respectively.…”
mentioning
confidence: 99%
“…Unusual root and root canal morphologies associated with molars have been recorded in several studies in the literature (2)(3)(4). Pécora et al (4) evaluated the anatomy of 370 maxillary molars and found that the maxillary first, second, and third molars showed three canals in 75%, 58%, and 68% of the teeth, respectively.…”
mentioning
confidence: 99%
“…Extra root may also present in seldom conditions as fused or separate root. 1 Several studies 7-13 confirmed the morphological variations in the root canal system in the palatal root of the maxillary second molar. Christie et al 5 proposed a classification for four-rooted maxillary second molars into three types.…”
Section: Introductionmentioning
confidence: 93%
“…Distobuccal and palatal canal usually have one canal each, although on rare occasions, either may have an extra canal. Extra root may also present in seldom conditions as fused or separate root . Stone and Stroner reported approximately 2% of maxillary molars with more than one palatal canal when examined 500 extracted molars, while Libfeld and Rotstein found only 0.4% incidence of extra palatal canal in 200 upper second molars and 1000 radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Devido à complexidade da anatomia interna da cavidade pulpar e ao fracasso nos tratamentos, o estudo e a compreensão da mesma tornaram-se ferramentas essenciais para auxiliar o profissional a enfrentar os desafios rotineiros do tratamento endodôntico 7 .…”
Section: Introductionunclassified